HUBUNGAN PERILAKU PENGGUNAAN PROTEKSI MATA DENGAN KELUHAN FOTOKERATITIS PADA PEKERJA LAS DI KECAMATAN PASAR REBO JAKARTA TIMUR TAHUN 2022 - Nur Aniza Amallia, (2022)
Welding is one of the jobs that have UV radiation hazards. Exposure to UV radiation can cause photokeratitis which is an acute inflammation of the cornea of the eye. The results of the preliminary study showed that the majority of informal sector welding workers in Pasar Rebo District experienced photokeratitis complaints. Most of the welders lack discipline in using eye protection. The purpose of this study was to determine the risk factors associated with photokeratitis complaints in welding workers in Pasar Rebo District, East Jakarta in 2022. This study used a cross sectional study design with a sample of 50 respondents. Data analysis used univariate and bivariate analysis (chi-square and simple logistic regression). The results showed that the proportion of photokeratitis complaints among welding workers was 78,0%. The results of the bivariate analysis showed that there was a relationship between the use of eye protection (p-value: 0,003; 0,041), years of service (p-value: 0,004), and knowledge of OHS (p-value: 0,007; 0,046) with complaints of photokeratitis. While the age of the workers (p-value: 0,129) was not associated with complaints of photokeratitis. Welders are advised to use eye protection with discipline and in accordance with applicable standards.